Big Issues, Young Minds: Preschool Teachers' Emotional Experiences and Coping Strategies in Climate Change Education - GÜDÜL, MERYEM DEMİR; YAĞAN, SEVCAN; AYDOS, EMİNE HANDE; Ülker, Ayça; Tatlı Dalioğlu, Seray; PARIM AÇIKALIN, KÜBRA (Springer, 2026)
Awareness-raising efforts around the climate crisis play a vital role in addressing environmental challenges but may also give rise to eco-anxiety. For early childhood educators, who are responsible for nurturing young children's emotional well-being, the ability to recognize, name, and respond to this complex emotional state is especially important. This study explores preschool teachers' practices related to the climate crisis, their emotional experiences in this context, and the emotional and pedagogical needs that arise in the process. Using a qualitative case study design, semi-structured interviews were conducted with eight preschool teachers. Thematic analysis revealed three key themes: CCE (Climate Change Education) practices, climate emotions, and emotions-aware practice needs. Findings indicate that although teachers did not explicitly plan climate-related activities, they frequently encountered its emotional dimensions through both formal instruction and daily interactions. They aimed to create emotionally safe environments and foster hope, often using these strategies to manage their own unease. While many struggled to articulate or define their emotional states, they tried to address children's concerns without intensifying distress. However, most reported uncertainty about how to navigate these challenges and emphasized the need for structured emotional support and training. Enhancing teachers' emotional awareness may enable more psychologically responsive climate education in early childhood settings.
Keywords: Climate Change Education; Eco-anxiety; Preschool Education; Teacher Emotional Awareness